Pengembangan Video Praktikum Sederhana Kimia Asam Basa Bermuatan Green Chemistry Untuk Siswa SMA Kelas XI - Risma Alfina Indriana; Agus Kamaludin (Jurnal Penelitian Pendidikan IPA, 2023)
Students' low critical thinking ability requires teachers to design the learning process creatively. One of the efforts teachers can make is integrating teaching materials with technology and learning models of Science, Technology, Engineering, and Mathematics (STEM). This study aims to develop an interactive electronic module containing STEM on the reaction rate material and determine the resulting module's quality. This research is development research (R&D) with a 4D development model (Define, Design, Develop, and Disseminate). The product is an interactive electronic module containing STEM in the form of HTML containing material, interactive quizzes, and STEM projects. The research instrument used was a quality assessment sheet for media experts, material experts, reviewers (high school chemistry teachers), and response sheets for class XI high school students. The results of the product quality assessment by media experts get a percentage of 96.7% in the very good category, material experts get 82.2% in the good category, and reviewers get 95.0% in the very good category. The students responded positively to the module with a percentage of 96.0%. Based on the assessment results and student responses, it can be concluded that the product developed is feasible to be used as an alternative media in the learning process on the reaction rate material to improve students' critical thinking skills